Pengelolaan Keuangan Pada UMKM Pusaka Keramik Plered - Ayu Nuradilah; Tria Melani; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
A business really needs capital or financing, and this capital can come from various sources. The purpose of this study is to determine the various sources of financing. Financial sources are financial sources that can be used to carry out investment activities. Every business or company has its own source of funding. Starting from internal and external estimates. The source of financing has a significant impact on the size and scale of a business, especially for SMEs. The method used in this study is a descriptive method that explains the sources of financing for MSMEs in Gunung Cupu village, namely Ceramic MSMEs based in Anjun village. SMEs with heritage ceramics receive internal sources of financing, ie. and alone.